Democratic Custom v International Customary Law - Roughan, Nicole (Victoria University of Wellington Law Review, 2007)
This article responds to the criticism that customary international law is undemocratic, by arguing that the criticism takes too narrow a view of conceptions of democracy and custom. The author suggests that democracy can be conceived as a process of participation rather than representation; and presents a conception of "compound custom" which combines the elements of custom as a source of law, as a mode of rights, and as a foundation of interaction. With this conception of compound custom in mind, customary international law has a greater democratic potential.